INDONESIA GOVERNMENT'S EFFORT TO FACE EU DIRECTIVE REGULATION CONCERNING PALM OIL IN EUROPE - Dini Tiara Sasmi (Andalas Institute of International Studies, 2020)
This article describes Indonesian Government effort dealing with new regulation in European Union, namely EU Directive which prohibit palm oil use for biodiesel. The European Commission has concluded in a regulation that palm oil use in biofuels will be reduced to zero by 2030. This regulation is based on allegations against oil palm plantation that causes excessive environmental damage. Environmental issues that arise as a result of the growing awareness of the international community in preserving the earth are often contrary to the wishes of a country in developing its economy. Campaigns from environmental activists in Indonesia highlight a lot about the palm oil industry which is often considered not sustainable and causes environmental damage. On the other hand, this campaign caused a negative reputation followed by the decline of Indonesia's palm oil exports to Europe. One of the regulations that arose was the EU Directive which was considered by the Indonesian government as discrimination against oil palm products and their derivatives. This article uses a qualitative analysis method. This study aims to analyze how the Indonesian government responds to the EU Directive regulation on Palm Oil which is considered detrimental to Indonesia's palm oil exports to Europe.